UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU PKN DI SMA NEGERI 1 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Arisman Sabir; Muhammad Hakiki (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2020)
Abstract —This research of background with observation early which is writer do/conduct in field, writer see various problem that happened in course of study of class like less maximal it him learn the the PKN in teaching. This matter seen moment the happening of study process take place. Pursuant to background of writer interest to check about " Effort of[is Make-Up Of Professional Interest of Teacher of PKN in SMAN 1 Six Beseting Sub-Province Field Pariah". this Type Research is research qualitative by using descriptive method. While used by technique is writer to determine informan that is technique of purposive sampling. Technique test authenticity of used by data is writer that is by data discount, presentation of data, and conclude or verification. Pursuant to result and observation interview writer with informan hence obtained by data that constraint faced in the effort improving professional interest of teacher of PKN in SMA Country 1 Six Beseting Sub-Province Field Pariah. ( 1) Less motivation, still many less raced teacher and motivat to be is powered of x'self, developing x'self profesionalitas and of memuthakirkan knowledge of them. ( 2) Limitation of medium, limitation of finansial represent especial constraint to effort development of education. Especially is to relating to accomplishment of requirement of education facilities and basic facilities, good of and also physical of non-fisik. ( 3) Many pressure, too tight and is stiff of him various obligatory bureaucracy all teacher, so that unable to develop creativity. And also strive improvement